ANALISIS INTERPERSONAL COMMUNICATION DALAM MEMEDIASI TRANSFORMATIONAL LEADERSHIP TERHADAP EMPLOYEE PERFORMANCE PADA PT. PELINDO MULTI TERMINAL BRANCH BELAWAN - Martin, Martin; Purjianto, Purjianto (UNIKA Santo Thomas, 2024)
Many factors can influence a person's performance, one of which is interpersonal communication. Interpersonal communication and performance are closely related and both are interrelated. Apart from interpersonal communication, transformational leadership can also influence employee performance where transformational leadership can strengthen or weaken employee performance. This research approach is qualitative with the Structural Equation Modeling (SEM) model. This approach is able to test the most ideal model in estimating endogenous variables. The population in this study were employees who worked at PT. Pelindo Multi Terminal Branch Belawan with a total of 278 employees, Transformational Leadership directly has a positive effect on Interpersonal Communication. Transformational Leadership directly has a significant effect on Employee Performance. Interpersonal Communication directly influences Employee Performance. Indirectly, Interpersonal Communication has no role in mediating Transformational Leadership on Employee Performance.